Roma and Sinti: dynamic identities and intercultural scenarios - Luca Bravi; Stefano Pasta; Greta Persico (Educazione Interculturale)
This contribution aims to provide an overview of studies on the relationship between education and Roma and Sinti groups, with a particular focus on the Italian pedagogical debate. It highlights key issues and approaches, starting with an examination of the historical and social relationship between Roma groups and pedagogy, emphasising the stigmatisation of these groups and the various processes of devisibilisation present in both academic discourse and public policy. The text also reviews the main Italian research conducted over the past fifteen years, which has addressed educational issues relating to these groups from multiple disciplinary perspectives. Topics discussed include schooling, continuing education for young Roma and Sinti, social and educational work, and the promotion of collective memory as an opportunity for emancipation.